CALCULATION OF STATISTICAL INDICATORS FOR EVALUATION OF SCIENTIFIC AND TECHNOLOGICAL ACTIVITIES IN THE FEDERAL BODIES OF EXECUTIVE POWER AND OF THE MINISTRY OF THE INTERNAK AFFAIRS OF THE RUSSIAN FEDERATION - Dmitriy V. Dianov; Yelizaveta N. Katasonova (Статистика и экономика, 2016)
Scientific and technical activity is part of development work. Is very important to plan scientic and technical activities. The article discusses the types of reports, calculation of statistical indicators, built charts and diagrams. These data will help to analyze the execution plans. Statistical indicators can be used in the Ministry of internal Affairs of the Russian Federation and other departments.